Visual Outcome after Anterior Segment Trauma of the Eye - Hamid Mahmood Butt, Muhammad Yasir Arfat (Pakistan Journal of Ophthalmology, 2010)
Purpose: To find out the final visual outcome (snellen visual acuity) after initial management of ocular trauma and to determine the etiological factors responsible for ocular trauma and extent of injury. Material and Methods: This study was conducted in the Department of Ophthalmology, Sir Ganga Ram Hospital/Fatima Jinnah Medical College, Lahore from June 2004 to December 2004. All these patients presented in the out patient department of Ophthalmology Sir Ganga Ram Hospital. Detailed history was taken. Complete clinical examination was done to record the findings and all patients were thoroughly investigated to reach the final diagnosis. All patients were treated on the basis of their diagnosis for the underlying cause. Surgical procedures were performed where appropriate. Every patient was followed for 6 months within the study period. Results: Fifty patients were included in the study. Forty two (84%) were male while 8 (16%) were female patients with male to female ratio 5.25:1. All patients were between 5-30 years of age (mean ± SD 15.94 ± 6.03). Different treatment options were used in the management of trauma. Conclusion: Complications of anterior segment trauma can be treated safely by medical and surgical methods.